2008
DOI: 10.1002/mus.21015
|View full text |Cite
|
Sign up to set email alerts
|

Muscle ultrasound in neuromuscular disorders

Abstract: Muscle ultrasound is a useful tool in the diagnosis of neuromuscular disorders, as these disorders result in muscle atrophy and intramuscular fibrosis and fatty infiltration, which can be visualized with ultrasound. Several prospective studies have reported high sensitivities and specificities in the detection of neuromuscular disorders. Although not investigated in large series of patients, different neuromuscular disorders tend to show specific changes on muscle ultrasound, which can be helpful in differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
331
2
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 366 publications
(349 citation statements)
references
References 95 publications
(208 reference statements)
12
331
2
4
Order By: Relevance
“…When considering the reliability of ultrasound as a measure of abdominal muscle function, our results with high ICC value of 0.957 in the control group are supported by previous work; 15,22 however, we observed less reliability in the SCI group. This finding may be because of difficulties in identifying fascial borders, as observed in the atrophied muscles of patients with Duchenne's muscular dystrophy or motor neuron disorders 23 and/or mislabelling of fascia borders owing to increased intramuscular fat, causing loss of contrast. 24 Compared with EMG, ultrasound measures of voluntary activity were highly specific (no false positive), but had poor sensitivity in detecting muscle activity when present.…”
Section: Discussionmentioning
confidence: 99%
“…When considering the reliability of ultrasound as a measure of abdominal muscle function, our results with high ICC value of 0.957 in the control group are supported by previous work; 15,22 however, we observed less reliability in the SCI group. This finding may be because of difficulties in identifying fascial borders, as observed in the atrophied muscles of patients with Duchenne's muscular dystrophy or motor neuron disorders 23 and/or mislabelling of fascia borders owing to increased intramuscular fat, causing loss of contrast. 24 Compared with EMG, ultrasound measures of voluntary activity were highly specific (no false positive), but had poor sensitivity in detecting muscle activity when present.…”
Section: Discussionmentioning
confidence: 99%
“…MUS findings including EI and MT in denervated hand muscles correlated with the severity of EMG abnormalities and facilitated the discrimination between moderate‐to‐severe muscle denervation and healthy hand muscles (Kim et al., 2016; Pillen et al., 2008; Simon et al., 2015). In this study, the quantitative MUS assessment on small hand muscles in patients with CIDP revealed that six out of 45 muscles with abnormally high EI and/or low MT suggested denervation following secondary axonal degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Pillen et al. insisted that MUS was equally or slightly less capable of detecting focal neuropathies than EMG, with a sensitivity estimated at 70% (Pillen et al., 2008). Simon et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this heterogeneous class of disorders, US has proved effective for measuring the muscle bulk. Semiquantitative scales based on muscle echogenicity have been used to estimate dystrophic changes in terms of fatty degeneration and connective tissue replacement [58][59][60]. In this class of disorders, US allows dynamic scanning during muscle contraction and may reveal spontaneous muscle activity (e.g.…”
Section: Musclementioning
confidence: 99%